Dapagliflozin promotes angiogenesis in hindlimb ischemia mice by inducing M2 macrophage polarization - Yang, Heng; Lan, Wanqi; Liu, Wu; Chen, Tingtao; Tang, Yanhua (Frontiers in Pharmacology, 2023)
Critical limb ischemia (CLI) is associated with a higher risk of limb amputation and cardiovascular death. Dapagliflozin has shown great potential in the treatment of cardiovascular disease. However, the effects of dapagliflozin on CLI and the underlying mechanisms have not been fully elucidated. We evaluated the effect of dapagliflozin on recovery from limb ischemia using a mouse model of hindlimb ischemia. The flow of perfusion was evaluated using a laser Doppler system. Tissue response was assessed by analyzing capillary density, arterial density, and the degree of fibrosis in the gastrocnemius muscle. Immunofluorescence and Western blot were used to detect the expression of macrophage polarization markers and inflammatory factors. Our findings demonstrate the significant impact of dapagliflozin on the acceleration of blood flow recovery in a hindlimb ischemia mouse model, concomitant with a notable reduction in limb necrosis. Histological analysis revealed that dapagliflozin administration augmented the expression of key angiogenic markers, specifically CD31 and α-SMA, while concurrently mitigating muscle fibrosis. Furthermore, our investigation unveiled dapagliflozin's ability to induce a phenotypic shift of macrophages from M1 to M2, thereby diminishing the expression of inflammatory factors, including IL-1β, IL-6, and TNF-α. These effects were partially mediated through modulation of the NF-κB signaling pathway. Lastly, we observed that endothelial cell proliferation, migration, and tube-forming function are enhanced in vitro by utilizing a macrophage-conditioned medium derived from dapagliflozin treatment. Taken together, our study provides evidence that dapagliflozin holds potential as an efficacious therapeutic intervention in managing CLI by stimulating angiogenesis, thereby offering a novel option for clinical CLI treatment.